2006
DOI: 10.1074/jbc.m511077200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Variations in Human Apolipoprotein E3 and E4

Abstract: There are three major apolipoprotein E (apoE) isoforms. Although APOE-⑀3 is considered a longevity gene, APOE-⑀4 is a dual risk factor to atherosclerosis and Alzheimer disease. We have expressed full-length and N-and C-terminal truncated apoE3 and apoE4 tailored to eliminate helix and domain interactions to unveil structural and functional disturbances. The N-terminal truncated apoE4-(72-299) and C-terminal truncated apoE4-(1-231) showed more complicated or aggregated species than those of the corresponding ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 59 publications
(49 reference statements)
2
52
0
2
Order By: Relevance
“…Sedimentation velocity studies confirmed that apoE3 and apoE4 were primarily tetrameric and monomeric in the presence of sub-micellar DHPC (4 mM) and micellar DHPC (20 mM), respectively (data not shown) (13,18). Fig.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Sedimentation velocity studies confirmed that apoE3 and apoE4 were primarily tetrameric and monomeric in the presence of sub-micellar DHPC (4 mM) and micellar DHPC (20 mM), respectively (data not shown) (13,18). Fig.…”
Section: Resultsmentioning
confidence: 79%
“…The 10-kDa C-terminal domain (residues 225-299) consists of three putative amphipathic ␣-helices. This C-terminal domain contains the major lipid binding region and in the absence of lipid mediates the self-association of apoE (12,17,18). In the absence of lipid, apoE and the isolated C-terminal domain exist primarily as tetramers, whereas the isolated N-terminal domain of apoE is monomeric (12,13,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ApoE4 has the highest affinity for the low-density lipoprotein receptor and is cleared fastest, whereas apoE2 has the lowest affinity for the low-density lipoprotein receptor and is cleared at a much lower rate, explaining the variation in plasma apoE levels. 26,27 Besides the influence of genetic variation on plasma apoE levels, phenotypic variation, such as dietary intake, has also been shown to influence plasma apoE levels. Several studies have reported increasing plasma apoE levels after the administration of diets containing saturated fatty acids, or fish and vegetable oil, 28,29 although others did not report such an association.…”
Section: Discussionmentioning
confidence: 99%
“…In a hierarchical approach, some of this knowledge has been incorporated into a secondary analysis in the form of a fixed constraint (for example, with the hybrid discrete/continuous distribution 29,[53][54][55], in combination of statistical analysis of the quality of fits obtained. However, in the present work we examined a more subtle approach, which permits the experimental data to override our expectation if they contain sufficient information contrary to our expectation.…”
Section: Introductionmentioning
confidence: 99%